Seasonal Bed Sediment Characteristics of the Kuala Sepetang River, Perak = Ciri-ciri Sediment Dasar Mengikut Musim di Kuala Sungai Sepetang, Perak (Universiti Kebangsaan Malaysia, 2008)
Bottom sediment samples from the Kuala Sepetang River, Taiping, Perak were analysed for the grain size in order to understand better the sedimentation processes in the estuary and along the river. The mean, standard deviation and skewness value of each sample were calculated by the moment’s method where each of every grain plot data was used to obtain the statistical information concerning the sedimentary population. In this study, there is no significant (p<0.05) relationship between sediment characteristic with the seasonal changes, but the mean particle size became a relatively smaller size during the monsoon season. Finer sediments (7.4 !) were dominated during monsoon season while coarser sediments (6.2 !) dominated during the dry season. The characteristics of deposited sediments at each station are much dependent upon the combination of physical forces such as freshwater runoff, tidal currents and waves.